Peran Auditor Internal Dalam Mencegah Fraud Asset Misappropriation : Literature Review - Galih Suryo Linuhur; Rizki Dwianto; Suparyono Suparyono; Sandy Aditya; Herlina Manurung (Jurnal Mutiara Ilmu Akuntansi, 2024)
This study aims to determine the role of internal auditors in preventing asset misappropriation fraud. The main topic of this research is the Covid-19 pandemic increasing the number of fraud in companies. This research method is in the form of a literature review method which originates from previous research originating from Google solar and books. This study uses qualitative methods and by using descriptive analysis. The results of the study show the role of internal auditors in preventing fraud by checking transaction validation and by checking physical documentation.